Physics based scalable inductance model for three-dimensional solenoid inductors. (September 2020) - Liu, Yang; Zhu, Zhangming; Liu, Xiaoxian; Lu, Qijun; Yin, Xiangkun; Yang, Yintang
Abstract: A physics based close form inductance model for three-dimensional (3-D) solenoid inductors with ground shileding is proposed in this letter. The expressions are derived in full consideration of partial self inductance and mutual inductance. The proposed model is extracted based on the process parameters and design parameters without any optimization. The 3-D inductor samples are fabricated on glass substrate by Through Glass Via (TGV) process. The accuracy of the proposed model is validated by comparing the results from the 3-D full-wave electromagnetic solver High Frequency Simulator Structure (HFSS) and measurement.